34‐2: Invited Paper: Analysis of Temperature Effect of RGB Mini/Micro LED Chips. Issue 1 (28th June 2022) - Sun, Yuanhao; Zhao, Jiawei; Ma, Junjie; Lin, Yicheng; Tian, Chao; Shi, Lingyun; Sun, Haiwei
Abstract : Mini/Micro light‐emitting‐diode (LED) emissive display has attracted wide range of attentions and has a good development prospect. One of the big challenges of Mini/Micro LED display is that the attenuation degree of luminous intensity of RGB chips with increasing working temperatures are different. In this work, we deeply analyzed this phenomenon and found out the factors contributing to that. It is found out that the attenuation degree of luminous intensity is directly related to the current density and material system of the chips. Moreover, the defect related non‐radiative recombination process and the different band structures between AlGaInP system and InGaN system are regarded as the main factors contributing to the different attenuation degree of luminous intensity with increasing working temperature of RGB chips.